Pengendalian Kualitas Derajat Pemisahan Hidrolisa Crude Fatty Acid Menggunakan Pendekatan Peta Kendali dan Kapabilitas Proses - Emil Salim P. Siregar; Poltak Evencus Hutajulu; Febrianti Sitorus (Politeknik AKA Bogor, 2022)
Acid Value and Saponification Value are used as parameters to measure Fatty Acid quality in Splitting Triglycerides from vegetable oils by hydrolysis process, Crude Palm Kernel Oil separation process to form Crude Fatty Acid and Glycerin in the Oleochemical Industry and is a reference for achieving the capability separation process in the Splitting Column by Splitting Degree of Hydrolysis method. From the results our study, we found that the tenth data from our test parameters observations are out of control but within specified range. Quality test parameters set for acid value and saponification value are in the range of 250 – 254 and 252–255 mg.KOH.g-1. The results of quality control at 252.411 and 253.55 mg.KOH.g-1 by a range 0.78 and 0.651, respectively for each parameter. The average of two parameters for hydrolysis conversion is 99.54 %, This result meets industry standards to produce good quality Crude Fatty Acid. The process capability value for Crude fatty acid production for parameter acid and saponification value are 1.45 and 1.30 respectively. Both values indicate that the hydrolysis separation process is running very well. The quality control Splitting Degree of Hydrolysis method using a control chart approach and process continuous capability for the resulting product can be used as a consideration in determining the quality of fatty acids and predicting fatty acid composition.